مرشدکی ضرورت اور مراقبہ :اردو سفر ناموں کا اختصاصی مطالعہ : The Need for a Mentor and Meditation: A Specialized Study of Urdu Travelogues - Muhammad Pervaiz; Dr Shabir Ahmad Jamee (AL-IDRAK JOURNAL, 2024)
Meditation and the need for a spiritual guide are essential aspects of spirituality that help an individual reach the depths of self-awareness and embark on a path of spiritual growth. These concepts are portrayed in various ways in Urdu travelogues, where travelers not only cross geographical boundaries but also undertake spiritual journeys.In Urdu travelogues, the role of a spiritual guide, or Murshid, is highlighted as that of a mentor and leader, who helps their disciples overcome worldly and spiritual difficulties with their guidance and counsel. The Murshid is often associated with a particular spiritual order or path, and through their presence, the disciple is shown the way to inner reform and a closer connection to God. The need for a spiritual guide is described in different contexts in these travelogues, where an individual relies on their guide for spiritual development. Meditation, a spiritual practice, aims to help a person achieve awareness of their inner truth and a closeness to God. In Urdu travelogues, meditation is depicted as an important spiritual practice, through which one seeks inner purity and strives to attain God's approval. It is seen as a means of achieving spiritual peace, mental tranquility, and freedom from worldly troubles.In Urdu travelogues, the references to both the spiritual guide and meditation teach us that spiritual progress requires not only the guidance of a Murshid but also the practice of meditation. These travelogues repeatedly emphasize that through the guidance of a Murshid and the practice of meditation, an individual can reach the depths of their spirituality, achieving success in both this world and the hereafter.Thus, in the light of Urdu travelogues, the importance of a spiritual guide and meditation can be understood as two essential pillars of spiritual development, providing the individual with the strength to change their destiny.